Change of mechanical vertebrae properties due to progressive osteoporosis: Combined biomechanical and finite-element analysis within a rat model - Mueller, Robert; Kampschulte, Marian; El Khassawna, Thaqif; Schlewitz, Gudrun; Huerter, Britta; Boecker, Wolfgang; Bobeth, Manfred; Langheinrich, Alexander C.; Heiss, Christian; Deutsch, Andreas; Cuniberti, Gianaurelio (Giovanni) (Medical & Biological Engineering & Computing, 2014)
For assessing mechanical properties of osteoporotic bone, biomechanical testing combined with in silico modeling plays a key role. The present study focuses on microscopic mechanical bone properties in a rat model of postmenopausal osteoporosis. Female Sprague-Dawley rats were (1) euthanized without prior interventions, (2) sham-operated, and (3) subjected to ovariectomy combined with a multi-deficiencies diet. Rat vertebrae (corpora vertebrae) were imaged by micro-CT, their stiffness was determined by compression tests, and load-induced stress states as well as property changes due to the treatment were analyzed by finite-element modeling. By comparing vertebra stiffness measurements with finite-element calculations of stiffness, an overall microscopic Young's modulus of the bone was determined. Macroscopic vertebra stiffness as well as the microscopic modulus diminish with progression of osteoporosis by about 70 %. After strong initial changes of bone morphology, further decrease in macroscopic stiffness is largely due to decreasing microscopic Young's modulus. The micromechanical stress calculations reveal particularly loaded vertebra regions prone to failure. Osteoporosis-induced changes of the microscopic Young's modulus alter the fracture behavior of bone, may influence bone remodeling, and should be considered in the design of implant materials. © 2014 International Federation for Medical and Biological Engineering.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Biomechanics; Bone histology; Osteoporosis; Rat model; Young's modulus